A self-monitoring microneedle patch for light-controlled synergistic treatment of melanoma - Chenyuan Wang; Yongnian Zeng; Kai-Feng Chen; Jiawei Lin; Qianqian Yuan; Xue Jiang; Gaosong Wu; Fubing Wang; Yong-Guang Jia; Wei Li (Bioactive Materials, 2023)
Melanoma is the most aggressive and malignant form of skin cancer. Current melanoma treatment methods generally suffer from frequent drug administration as well as difficulty in direct monitoring of drug release. Here, a self-monitoring microneedle (MN)-based drug delivery system, which integrates a dissolving MN patch with aggregation-induced emission (AIE)-active PATC microparticles, is designed to achieve light-controlled pulsatile chemo-photothermal synergistic therapy of melanoma. The PATC polymeric particles, termed D/I@PATC, encapsulate both of chemotherapeutic drug doxorubicin (DOX) and the photothermal agent indocyanine green (ICG). Upon light illumination, PATC gradually dissociates into smaller particles, causing the release of encapsulated DOX and subsequent fluorescence intensity change of PATC particles, thereby not only enabling direct observation of the drug release process under light stimuli, but also facilitating verification of drug release by fluorescence recovery after light trigger. Moreover, encapsulation of ICG in PATC particles displays significant improvement of its photothermal stability both in vitro and in vivo. In a tumor-bearing mouse, the application of one D/I@PATC MN patch combining with two cycles of light irradiation showed excellent controllable chemo-photothermal efficacy and exhibited ∼97% melanoma inhibition rate without inducing any evident systemic toxicity, suggesting a great potential for skin cancer treatment in clinics.